How to use information te chnology (IT) wisely for early childhood language education? (International Conference on Computers in Education, 2013)
To examine the uses of information technology (IT) in early childhood language education, this paper reviews 34 studies to synthesize the current literature. Considerable insights are provided by these conceptual and empirical studies. A synthesis is given of with regards to the different pertinent IT features and how young children’s language development is influenced by these features. These pertinent IT features include digital picture, video, audio clips, website, game, Microsoft office, electronic file, blog and diagram. The findings are then based on literature to underpin how to use IT wisely for the language development of young children. The synthesis would like to highlight that, the nine pertinent IT features are somehow related to young children’s language developmental domains, and ways to use these features. This seems probable to shed lights on future IT research, design, and implications in young children’s language development.